A combination of two human monoclonal antibodies cures symptomatic rabies. Issue 11 (18th September 2020) - de Melo, Guilherme Dias; Sonthonnax, Florian; Lepousez, Gabriel; Jouvion, Grégory; Minola, Andrea; Zatta, Fabrizia; Larrous, Florence; Kergoat, Lauriane; Mazo, Camille; Moigneu, Carine; Aiello, Roberta; Salomoni, Angela; et al.
Abstract: Rabies is a neglected disease caused by a neurotropic Lyssavirus, transmitted to humans predominantly by the bite of infected dogs. Rabies is preventable with vaccines or proper post‐exposure prophylaxis (PEP), but it still causes about 60, 000 deaths every year. No cure exists after the onset of clinical signs, and the case‐fatality rate approaches 100% even with advanced supportive care. Here, we report that a combination of two potent neutralizing human monoclonal antibodies directed against the viral envelope glycoprotein cures symptomatic rabid mice. Treatment efficacy requires the concomitant administration of antibodies in the periphery and in the central nervous system through intracerebroventricular infusion. After such treatment, recovered mice presented good clinical condition, viral loads were undetectable, and the brain inflammatory profile was almost normal. Our findings provide the unprecedented proof of concept of an antibody‐based therapeutic approach for symptomatic rabies. Synopsis: Rabies is an invariably fatal disease after the rabies virus has invaded the central nervous system and clinical signs have been manifested. This study brings the proof‐of‐concept that a cocktail of human monoclonal antibodies (mAbs) can cure symptomatic rabies. Intramuscular + intracerebroventricular administration of RVC20/RVC58 mAbs cures symptomatic rabies in a mouse model. Continuous administration of RVC20/RVC58mAbs directly in the central nervous system is crucial to treatment success. RVC20/RVC58 mAbs therapy promotes rabies virus clearance from infected brains in vivo and restoration of normal clinical condition in infected mice. Abstract : Rabies is an invariably fatal disease after the rabies virus has invaded the central nervous system and clinical signs have been manifested. This study brings the proof‐of‐concept that a cocktail of human monoclonal antibodies (mAbs) can cure symptomatic rabies.